Relationship Between Teachers' Presentations and Students Conceptual Understanding of Some Biology Topics - B. Barquilla, Manuel (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The study explores the possibility of establishing the congruence of teachers' (n=6) representations of content knowledge and students' (n=222) conceptual understanding of some high school topics in biology. It aims to determine the subsequent effect of teachers' representation of content knowledge on students' conceptual understanding and establish their relationship. Relationship in this study refers was matching of the students' with the teachers' representation of content knowledge. This is done by comparing what the teacher have in mind (as expressed in their concept maps) with what the students have in mind (as expressed in their concept-maps) and determining whether there is agreement in the concept of the two groups. The results of the correlation analysis indicate a Kendall's Tau value of 80 significant at a = .05 when all topics are combined. The highest Kendall's Tau coefficient value among the topics studied is .733 in Non Mendelian Genetics, which was considered as the least knowledgeable topic in the teachers' knowledge structure (Barquilla, 2002). It is highly probable, therefore, that those teachers exerted extra effort to make their representation of genetics content interesting and challenging to students, to the point that the latter understood the concept clearly.